INVESTIGASI PENGARUH PEMANFAATAN TANDAN BUAH KOSONG SEBAGAI BAHAN BAKAR BOILER TERHADAP PEMBENTUKAN GAS RUMAH KACA - Amiral Aziz (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2000)
The gas produced in solid waste disposal sites, particularly CH4 can be a local environmental hazard if precaution are not taken to prevent uncontrolled emissions or migration into surrounding land. Gas can migrate from solid waste disposal sites either laterally or by venting to atmosphere, causing vegetation damage and unpleasant odors at low concentration, while at concentration of 5-15 per cent in air, the gas may be form explosive mixture.Recently, a forest fire on the Indonesian islands of Sumatra and Kalimantan left not only Indonesia but neighboring countries as well covered under a thick cloud of haze. Some palm plantations and palm oil refineries once disposed of palm oil waste (Empty Fruit Bunches ) by drying them in ovens and then burning them in fields. This paper discusses some results of the experimental and theoretical investigations which conducted to examine effects of the utilization of palm oil wastes particularly Empty Fruit Bunches as the fuel of boiler on greenhouse gas emission.